Dashboard design and the 'datafied' driving experience. Issue 2 (July 2021) - Hind, Sam
In this article, I consider how the redesign of vehicle dashboards has restructured car-related data processes. I do so by charting the emergence of two such processes enabled by the redesign of vehicle dashboards: firstly, the transformation of 'geodata' into 'navigational data' with the integration of voice-activated navigation systems into vehicle dashboards, and secondly, the transformation of 'vehicle data' into 'driving data' in the convergence, and customization, of dashboard features and functionality. Both transformations are enabled through strategic design decisions, persuading drivers to participate in novel practices they might otherwise not. Firstly, in that voice-activation is depicted as a seamless, unmediated interface between the normal, natural speech of a driver, and the vehicle itself. Secondly, through the strategy of control, the driver is persuaded to believe they have full(er) customizable power within, and of, the vehicle. The systems discussed here – a voice-activated navigation system built on the What3words platform, and a 'widescreen' dashboard in a range of Mercedes-Benz vehicles – are representative of broader efforts within the automotive industry to cultivate a newly 'datafied' driving experience.